Fallacies in Aggregate Demand/Supply Analyses - Amit Bhaduri; Kazimierz Laski; M. Riese (The Vienna Institute for International Economic Studies (wiiw), 1994)
The aggregate demand (AD)/aggregate supply (AS) framework as presented in almost all textbooks is logically inconsistent, because it seperates the demand side from the supply side. Due the the circular flow nature of the macroeconomic process, however, production/supply and income/demand cannot be dichotomised. Specifically it is shwon that the AD/AS apparatus implies incompatible levels of employment for all positions out of equilibrium. A reformulated aggregate demand schedule, which avoids these inconsistencies, typically has a positive slope; together with the positively sloped AS curve equilibrium thus becomes unstable.
Keywords: 330; Aggregate demand (AD); aggregate supply (AS); incompatibility of AD/AS; slope of AD curve; instability of AD/AS equilibrium